SÍNTESE DE ALQUINOS TERMINAIS A PARTIR DE AMINAS PARA-SUBSTITUIDAS CONTENDO O NÚCLEO ORTO-NAFTOQUINOIDAL - SILVA, Carlos Henrique; DA SILVA, Natan; COUTO, Aliziane; OLIVEIRA, Tarsila; OLIVEIRA, Geane; VALENÇA, Wagner (ANAIS DO ENIC, 2025)
.